Consumer information development and use. - McCormack, Lauren A.; Garfinkel, Steven A.; Schnaier, Jenny A. (Health Care Financing Review)
Part of a special section on consumer information in a changing health care system. A study was conducted to investigate the types of information that consumers need to choose a health plan and use the plan effectively. Drawing on the results of case study interviews with 24 organizations, it was found that ten of them included consumer satisfaction ratings and performance measures based on medical records and that another four organizations developed materials with only consumer satisfaction ratings. Printed materials were found to be the most commonly used mode of communication of information to consumers, although other mechanisms were also used. It is concluded that, on the whole, the materials have not been rigorously appraised and that evaluations are needed to ascertain whether consumers find the information useful and how different individuals would prefer to receive the information.